The effect of quality management system (ISO 9001) on operational performance of various organizations in Indonesia - Arfan Bakhtiar; Aditya Nugraha; Hery Suliantoro; Darminto Pujotomo (Cogent Business & Management, 2023)
An organization improves its performance by implementing ISO 9001, but there are not many scientific journals that discuss this. The purpose of this article is to examine the effect of the quality management system (ISO) 9001 on organizational performance to achieve business sustainability. This study examines four variables, namely ISO 9001 certification planning, organizational commitment, application of procedures on organizational performance and quality culture as mediating variable. Data collection was conducted in the form of a survey by e-mailing the questionnaire to 1000 ISO 9001 certified organizations selected using the purpose sampling technique. This research used a closed questionnaire and a Likert scale of 1-5. Data calculation utilized a Partial Least Squares (PLS) analysis to distinguish outer and inner model analyses, as well as to test the hypotheses. The results show that ISO 9001 certification planning, organizational commitment, and application of procedures have a significant effect on quality culture. ISO 9001 certification planning and organizational commitment do not have a significant effect on operational performance, but the application of procedures and quality culture significantly influence operational performance. It is clear that an increase in organizational performance greatly influences by ISO 9001 implementation and a quality culture as a mediating variable.
Keywords: 650; certification planning; ISO 9001; organizational performance; procedure application; quality culture; quality management